The determinants of Brazilian corporate credit ratings: how did the market react to sovereign downgrades? - Rocca, Nicolò (2017)
First and foremost, I would like to thank my supervisors, Professor Miguel Ferreira at Nova SBE and Professor Ricardo Rochman at FGV-EESP, for their constructive feedback and insightful guidance throughout the research. I would also like to thank all the members of International Master in Finance Brazil-Europe for providing me deep knowledge in the areas of corporate finance, quantitative analysis, management of financial institutions and investment banking necessary to excel in today’s international financial markets. Furthermore, I would also like to express gratitude for the extensive facilities provided by the institutions, for the staff and for the IMF program that blends analytical, applied and scientific rigor. I would like to express my most sincere gratitude to my family for providing me continuous encouragement throughout my years of university. Thanks to all of them.